Preparation and evaluation of a deoxycholic‐calix[4]arene hybrid‐type receptor as a chiral stationary phase for HPLC. Issue 9 (9th February 2018) - Yaghoubnejad, Sadegh; Tabar Heydar, Kourosh; Ahmadi, Seyyed Hamid; Zadmard, Reza; Ghonouei, Nima
Abstract: We report the synthesis and enantioseparation characteristics of two novel covalently immobilized deoxycholic acid derivatives as chiral stationary phases for high‐performance liquid chromatography. In the structure of the first stationary phase, the 3‐position of deoxycholic acid is substituted with a 3, 5‐dinitrophenylcarbamoyl group and the second one has an additional calix[4]arene attached to the carboxylic group of the deoxycholic acid. The chromatographic performance of the stationary phases was evaluated with enantioseparation of N ‐(3, 5‐dinitrobenzoyl)‐dl ‐leucine, N ‐(3, 5‐dinitrobenzoyl)‐dl ‐valine, omeprazole, diclofop‐methyl, dl ‐mandelic acid and ( RS )‐pregabalin. Comparison of the performance characteristics of the prepared chiral stationary phases provided evidence for the active involvement of the calix[4]arene unit in the chiral recognition process. Both stationary phases are chemically bonded to the silica and can be used in both normal‐phase and reversed‐phase modes.